Intensified training supersedes the impact of heat and/or altitude for increasing performance in elite rugby union players - Racinais, S.; Périard, J. D.; Piscione, J.; Bourdon, P. C.; Cocking, S.; Ihsan, M.; Lacome, M.; Nichols, D.; Townsend, N.; Travers, G.; Wilson, M. G.; Girard, O. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To investigate whether including heat and altitude exposures during an elite team-sport training camp induces similar or greater performance benefits.